Biosignal processing apparatus and biosignal processing method - Cho, Seongho; Lee, Joonhyung; Kim, Sangkyu (2019)
Provided are a biosignal processing apparatus and a biosignal processing method. The biosignal processing apparatus includes: a first measurement module configured to detect a biosignal of a subject in a non-invasive manner in response to the biosignal processing apparatus being in contact with the subject; a second measurement module configured to measure a contact state with respect to the subject; and a controller configured to determine whether the contact state is equal to or greater than a reference value.